Economics/by Fred Rogers Fairchild, Edgar Stevenson Furniss and Noraman Sydeney Buck - Fairchild, Fred Rogers (New York, 1948)
The present book is a shorter edition of our two-volume Ele mentary Economics. It has been written in response to the demand for an elementary textbook in economics similar in character to the longer work but of length suitable for use in half-year courses or in those full-year courses which use a general foundation text followed by selected special books. As regards purpose, balance of topics, plan, and style, the two books are generally alike.
Keywords: Economics